The Relationship between Osteoporosis and Osteoarthritis of the Knee: A Report of 2 Cases with Suspected Osteonecrosis - Akira Horikawa; Naohisa Miyakoshi; Yoichi Shimada; Hiroyuki Kodama (Case Reports in Orthopedics)
Knee specimens of two osteoporotic patients who underwent unilateral knee arthroplasty for suspected osteonecrosis of the knee were examined histologically. Preoperative findings of magnetic resonance images in both patients were consistent with the diagnosis of osteonecrosis of the medial femoral condyles, although plain X-rays showed minimal degenerative changes. In both patients, preoperative bone mineral densities of the femoral condyle and proximal tibia of the affected side were lower than those of the unaffected side. Pathological examination of the resected femoral condyle and proximal tibia showed almost intact joint cartilage, healing of the collapsed subchondral bone, and significant trabecular bone loss. Histologically, no evidence of osteonecrosis, including empty lacunae of the trabecular bone, was observed. These findings indicated that subchondral bone collapse caused by osteoporosis, but not osteonecrosis, initiated the osteoarthritic change of the affected knee. This report emphasizes that there may be cases of progressive local osteoarthritis caused by fracture of subchondral bone because of osteoporosis.